Does Covid 19 affect the income of Muslim entrepreneurs? Case study of culinary MSMEs in Surakarta - Farah Dewayanti; Ari Rudatin; Andika Ridha Ayu Perdana (Review of Islamic Social Finance and Entrepreneurship)
Purpose – This study aims to analyze the influence of sales turnover, business age, number of employees, operating hours, and Covid-19 on the income of Micro, Small and Medium Enterprises (MSMEs) in the culinary sector in the City of Surakarta, Central Java. Method – This study adopts a quantitative approach and uses primary data. Data were collected using a purposive random sampling technique. The analysis was performed using the E-Views method with multiple linear regression following the Mackinnon White and Davidson (MWD) model. The dependent variable is MSME income in the culinary sector, while the independent variables include sales turnover, business age, number of employees, operating hours, and the impact of Covid-19 Findings – The results show that sales turnover, number of employees, and the impact of Covid-19 have a positive influence on MSME income in the culinary sector of Surakarta City. However, business age and operating hours have a negative influence on MSME income. Implications – These findings have important implications for Muslim entrepreneurs striving for innovation in seizing opportunities during crises. The ability of Muslim entrepreneurs to utilize technology-based marketing can increase their income during crises. Technology makes indirect selling more accessible to MSMEs to increase income because the market reach is broader. Originality – This research differs from previous studies in terms of the research location, which is the city of Surakarta. The data used are primary data during the Covid-19 outbreak, and the respondents are Muslim entrepreneurs managing MSMEs in the city of Surakarta.